2008
DOI: 10.1021/jp710532z
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Structure and Conformations of para-Methylbenzene Sulfonamide and ortho-Methylbenzene Sulfonamide:  Gas Electron Diffraction and Quantum Chemical Calculations Study

Abstract: The molecular structure and conformational properties of para-methylbenzene sulfonamide (4-MBSA) and ortho-methylbenzene sulfonamide (2-MBSA) have been studied by gas electron diffraction (GED) and quantum chemical methods (B3LYP/6-311+G** and MP2/6-31G**). Quantum chemical calculations predict the existence of two conformers for 4-MBSA with the S-N bond perpendicular to the benzene plane and the NH2 group either eclipsing or staggering the S-O bonds of the SO2 group. Both conformers possess CS symmetry. The e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
26
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 13 publications
(22 reference statements)
3
26
0
Order By: Relevance
“…Importantly, if we consider the position of the sulphur bound oxygen atoms with respect to the piperazine nitrogen substituents, family I and IV present the anti and the fully eclipsed conformations, respectively ( Figure 3B). Thus, in agreement with previously reported results on benzosulfonamide derivatives [35][36][37] the two most favoured families of conformers are I and IV, with family I (i.e., anti conformation of the oxygen atoms with respect to the piperazine nitrogen substituents) representing the GM family, as found in the crystal structure of N,N-dimethyltoluene-p-sulfonamide [38].…”
Section: Computational Studies and Sar Analysissupporting
confidence: 92%
See 1 more Smart Citation
“…Importantly, if we consider the position of the sulphur bound oxygen atoms with respect to the piperazine nitrogen substituents, family I and IV present the anti and the fully eclipsed conformations, respectively ( Figure 3B). Thus, in agreement with previously reported results on benzosulfonamide derivatives [35][36][37] the two most favoured families of conformers are I and IV, with family I (i.e., anti conformation of the oxygen atoms with respect to the piperazine nitrogen substituents) representing the GM family, as found in the crystal structure of N,N-dimethyltoluene-p-sulfonamide [38].…”
Section: Computational Studies and Sar Analysissupporting
confidence: 92%
“…This is particularly important for sulphonamide derivatives which present electron withdrawing substituent on the sulphur atom, since it has been previously demonstrated that, in this case, the different conformers can be considered as rather rigid molecules due to a high barrier of internal rotation around the S-N bond [35], and that this effect is enhanced in the presence of an ortho-substituted phenyl ring with respect to unsubstituted or para-substituted ones [37].…”
Section: Computational Studies and Sar Analysismentioning
confidence: 99%
“…According to this study, the saturated vapor over solid benzene sulfonamide at a temperature of 150(5) C consists predominantly of a conformer with the SAN bond perpendicular to the benzene ring and the NH 2 group eclipsing the SO 2 entity. Calculations also show that the sterically unfavorable orientation of the NH 2 group is stabilized by intramolecular hydrogen bonds between O and H atoms of the sulfonamide group [49].…”
Section: Introductionmentioning
confidence: 95%
“…The crystal structures of BSA [4], ortho-MBSA (or 2-MBSA) [5], and para-MBSA (or 4-MBSA) [6] were studied by X-ray diffraction (XRD). Earlier, we reported the results of gas-phase electron diffraction (GED) study on the molecular structures of free molecules mentioned above [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…BSA [7] and 4-MBSA [8] have two conformers each: the S-N bond is oriented orthogonally with respect to the benzene ring while the N-H and S=O bonds of the SO 2 NH 2 groups either eclipse each other (eclipsed conformers) or are in staggered positions (staggered conformers). Unfortunately, the GED method did not allow to reliably determine a quantitative ratio between the conformers in case of 4-MBSA because of low scattering power of the hydrogen atom in the NH 2 group.…”
Section: Introductionmentioning
confidence: 99%